Virtual reality and cognitive function rehabilitation after traumatic brain injury: a systematic review - Nemanja Lakicevic; Bogdan Andjelic; Marko Manojlovic; Ambra Gentile; Antonino Bianco; Antonio Paoli; Sergey Leonov; Alexander Pashchenko; Patrik Drid (European Journal of Translational Myology)
Traumatic Brain Injury (TBI) is the leading cause of injury-related death worldwide. In recent years, Virtual Reality (VR) has emerged as a promising diagnostic and treatment tool capable of improving Cognitive Function (CF) after TBI. We sought to review the literature on this issue systematically. Web of Science, PubMed and PsycINFO were screened for relevant literature. Only randomized control trials whereby TBI-affected individuals underwent VR training and control groups received standard rehabilitative care were included. Screening, quality appraisal and data extraction were conducted by independent reviewers using a standardized protocol. Six studies of ~300 participants met the inclusion criteria and showed that both groups improved their overall CF post-intervention. However, non-immersive and semi-immersive VR groups had markedly better scores in all of the cognitive domains measured when compared to non-VR groups. VR is a potent post-TBI rehabilitative tool that can improve CF in this population and facilitate the return-to-work process. Future studies should adopt a similar design yet use fully immersive VR to enhance CF potentially to a greater degree.